A rare presentation of extra pulmonary tuberculosis in neck (isolated level-VI cervical lymph node tuberculosis) - Bhatt, Chandani D.; Shah, Ishita; Odedara, Ramde; Modi, Niral (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
One of the most common varieties of extra pulmonary tuberculosis is tuberculosis lymphadenitis. This was the case report of a 40-year-old female who presented with complaint of neck swelling and voice change and was later diagnosed with an isolated extra-pulmonary level-VI cervical lymph node tuberculosis. The diagnosis was made by histopathology and PCR and patient was then started with anti-tuberculosis therapy.